Some Characterizations of $VMO(\mathbb{R}^n)$ (Analysis in Theory and Applications, 2014)
In this paper we give three characterizations of $VMO(\mathbb{R}^n)$ space, which are of John-Nirenberg type, Uchiyama-type and Miyachi-type, respectively.